Physical characteristics of several corn varieties and the interaction between planting patterns and varieties on pest attacks Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) and ant population Oecophylla smaragdina (Fabricius) - Fattah, Abdul; Widiarta, I. Nyoman; Yasin, M.; Mulia, Sahardi; Nappu, M. Basir; Sipi, Surianto; Hannan, Muhammad Fitrah Irawan; Najamuddin, Erwin; Idaryani, Idaryani; Herniwati, Herniwato; Syafruddin, Syafruddin; Paesal, Paesal; et al. (Frontiers in Sustainable Food Systems, 2025)
The selection of superior maize varieties and appropriate planting arrangements plays a crucial role in improving crop productivity and managing pest infestations. Spodoptera frugiperda (fall armyworm) is a major pest in maize cultivation, while natural predators such as Oecophylla smaragdina (weaver ants) offer potential for biological control. This study aimed to examine the effects of two planting models and seven maize varieties on agronomic traits, grain yield, pest damage, and predator abundance. A split-plot randomized block design was implemented with three replications. The main plots consisted of two planting arrangements: the conventional tile pattern (70 cm × 40 cm) and the legowo 2:1 system ((50 cm × 35 cm) × 90 cm). Sub-plots included seven maize varieties: Srikandi Kuning, Pulut Uri, Provit A1, Anoman, Srikandi Ungu, Bisma, and Sukmaraga, each grown in 150 m2 plots. Results showed significant varietal differences in plant height (168.78 -219.30 cm), leaf area (6.60 -7.85 cm²), flowering time (45.33 -49.00 days), and ear height (89.42 -119.32 cm). The legowo 2:1 planting model significantly increased grain yield (7.89 t ha−1) compared to the tile model (5.38 t ha−1 and reduced leaf (19.12% vs. 21.26%) and cob damage (11.58% vs. 13.09%) by S. frugiperda. Larval density varied among varieties, with Bisma showing the lowest incidence (0.43 larvae per plant; 12.32% leaf damage, 8.80% cob damage) and Sukmaraga the highest (1.23 larvae per plant; 25.23% leaf, 15.03% cob damage). Weaver ant abundance was negatively correlated with pest population and damage intensity. Biplot analysis indicated that Bisma performed best under the legowo system, while Anoman showed optimal performance under the tile model. These findings suggest that integrating the appropriate planting configuration with resistant maize varieties can enhance productivity and reduce pest damage, offering valuable strategies for sustainable maize cultivation.